Market discipline in banking : theory and evidence - Kaufman, George G. (Amsterdam, the Netherlands ; San Diego, CA, USA : Elsevier JAI, 2003)
The resolution of a large complex financial organization presents numerous problems, including organizational complexity, opacity of positions, and conflicting legal jurisdictions.
Papers presented at special sessions at the annual meetings of the Financial Management Association International in Dublin, Ireland, in June 2003, and of the Western Finance Association in Vancouver, Canada, in July 2003.
Includes bibliographical references.
aia 11/8/16, ijb 07/03/2019
Loan
Keywords: Banks and banking; Bank management